Nurith Aviv 5 films, 1 livre = Mi-śafah le-śafah - Aviv, Nurith 1945- (Éd. Montparnasse, 2011)
Vaters Land: "Starting from Sigmund Freud's definition of mourning and from Hannah Arendt's observation of the behavior of German intellectuals in 1933, Nurith Aviv lets her friends in Germany speak about what, according to them, has been irrevocably lost. In the background, a traveling shot of 30 minutes, a trip with the S-Bahn through Berlin, hometown of her Jewish ancestors"--http://www.viennale.at/cgi-bin/viennale/archiv/film.pl?id=951&lang=en. - Lauréat du Prix Edouard Glissant 2009